Social Problems of Modern Society in Applying Islamic Law in Aceh : Tracing The Past Culture Society Aceh in The Manuscript - Aida Hayani (Justicia Islamica, 2018)
The implementation of Islamic law in this modern age seems to be strange among moslems. It is the caused by most of them are opposed and if it is implemented a scare among the social society perfectly. Besides, they are still not integrated to implement the Islamic law, most of them still have not taken Islam as the path of life yet. So, as if it is not their responsibility to keep it goes along Reviews their life, and Neither to take control and implement it perfectly and truelly in their daily life. This research is Aimed to upgrade the knowledge and understanding of public society that implementation of Islamic law. Perfectly is Necessary to Anticipate the problems in this modern age. The local policy is getting reduce by coming the modern culture. As a sample, Achehnese most of the teenagers who live in urban can not understand to communicate by using Achehnese language well and most of the attitude of Achehnese is getting dissappear from their ancestor inheritance. There are many manuscripts about Achehnese culture in meseum and dayah (Traditional Islamic boarding school) Described roomates Achehnese the culture of the which is bordered by Islamic values. Base on the previous statements, the goverment of Aceh is expected to apply the Islamic law in Aceh perfectly among all society.